Shifts from competition to facilitation between a foundation tree and a pioneer shrub across spatial and temporal scales in a semiarid woodland - Sthultz, Christopher M (The New phytologist, 2007)
* Theoretical and empirical research has supported the hypothesis that plant-plant interactions change from competition to facilitation with increasing abiotic stress. However, the consistency of such changes has been questioned in arid and semiarid ecosystems. * During a drought in the semiarid south-western USA, we used observations and a field experiment to examine the interactions between juveniles of a foundation tree (Pinyon pine, Pinus edulis) and a common shrub (Apache plume, Fallugia paradoxa) in replicated areas of high and low stress. * The presence of F. paradoxa reduced P. edulis performance at low-stress sites, but had the opposite effect at high-stress sites. However, the intensity of the interactions depended on temporal variation in climate and age of P. edulis. Both above- and below-ground factors contributed to competition, while only above-ground factors contributed to facilitation. * These results support the hypothesis that interactions can change from competition to facilitation as abiotic stress increases in semiarid environments. A shift from competition to facilitation may be important for the recovery of P. edulis and other foundation species that have experienced large-scale mortality during recent droughts